Wikipampa: suporte à gestão do conhecimento no sistema de bibliotecas da Universidade Federal do Pampa - Medeiros, Marlucy Farias (2017)
The present project has as a research theme the integration of networked educational technologies in the management of knowledge in university library systems and had the objective of integrating a wiki tool to support the knowledge management in the Library System (SISBI) of the Federal University of Pampa (UNIPAMPA). This study focuses on educational networking technologies for innovation and democratization of education and is part of the research line of management of networked educational technologies. In this way, we proposed an applied nature research with procedures based on the Design-Based Research (DBR) method that took place in four phases, with three iterative cycles. For data collection, survey questionnaires were applied and participant observation was carried out for the purpose of recording the interventions. As a basic theory, we used the method of converting the combination knowledge, the basic elements of knowledge management in university libraries and the concept of produsage. The diagnosis was made through the application of the first questionnaire survey of open and closed questions with servers of the Library System. After analyzing the diagnostic data, a survey was made of the infrastructure needs for the implementation of the tool and the preparation of a proposal for the Rectory and Library Coordination of the university. For the implementation and development of the proposal, the categorization of the WikiPampa platform was performed. The creation of a user manual, with usage guidelines and policies, is the final product generated from this research, in addition to the own WikiPampa collaborative platform, tutorial videos, and design principles for integration. As a result, the integration of the wiki tool as support for knowledge management is possible and the design principles for integration were developed, the possibilities and challenges of this integration were also listed. Therefore, WikiPampa can provide the retention and sharing of information as a viable and sustainable alternative to support knowledge management in the university library system.